A Concepção de liberdade na filosofia política de Hannah Arendt - Barbosa, Kherlley Caxias (Universidade do Vale do Rio dos Sinos, 2017)
In this work, I support the thesis there are three dimensions in Arendt‟s conception of freedom: the political dimension, in which freedom is actualized in action; the ontological dimension, in which natality is considered as the source of free human activities; the inner or mental dimension, in which freedom is the fundamental characteristic of the activities of thinking and willing. These three dimensions are intertwined by a common notion: the human capacity to initiate something new. Arendt chose freedom as the fundamental theme of her thinking from her turn to politics to her later writings. I maintain that the notion of freedom is the guiding thread that pervades all his works on human activities and on the human condition. Arendt's interpreters emphasize the centrality of freedom in her political philosophy, but they do not show how the human condition of freedom is actualized in all dimensions of freedom, because they reduce freedom to the political dimension (Kateb and Dana Villa), do not deal with thinking and willing which of the mental dimension of freedom (Passerin D'Entreves), enunciate the relation of the ability to begin with human activities in an ambiguous way (Kohn), adopt a concept of freedom that does not yield the common notion of freedom that Arendt uses to describe human activities (Young -Bruhel). By distinguishing the three dimensions of freedom and by pointing out the notion common to all of them, I establish a way of understanding Arendt's freedom, which seeks to unveil his conception of freedom, and which emphasizes the anthropological trait of her descriptions of the activities of human faculties and her reflections on the human condition. This work was structured to deal with each of the dimensions of freedom. It begins with the origins of Arendtian political thought in the critical confrontation with existential philosophy and in the discussion of the Jewish Question, shows the annihilation of freedom by totalitarian government, and presents each of the dimensions of freedom, first considering the political and ontological dimensions of action, revolution and natality and concluding with the analysis of the inner dimension of freedom, presenting the activities of willing and thinking.
Keywords: Arendt; Liberdade; Ação; Pensamento; Natalidade; Vontade; Arendt; Freedom; Action; Thinking; Willling; Natality; ACCNPQ::Ciências Humanas::Filosofia